2009
DOI: 10.1152/japplphysiol.90821.2008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of individual skeletal muscle activity by glucose uptake during pedaling exercise at different workloads using positron emission tomography

Abstract: Skeletal muscle glucose uptake closely reflects muscle activity at exercise intensity levels <55% of maximal oxygen consumption (VO2max). Our purpose was to evaluate individual skeletal muscle activity from glucose uptake in humans during pedaling exercise at different workloads by using [18F]fluorodeoxyglucose (FDG) and positron emission tomography (PET). Twenty healthy male subjects were divided into two groups (7 exercise subjects and 13 control subjects). Exercise subjects were studied during 35 min of ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 22 publications
(23 reference statements)
3
47
1
Order By: Relevance
“…Other researchers have reported that the iliopsoas muscle is an important contributor during pedaling. 12 The rectus femoris muscle, which crosses the hip joint like the iliopsoas muscle, but in addition crosses the knee joint, is considered a top transition-extensor muscle, where "top" refers to the top dead center of the crank revolution. 13 Increased rate of force development in the hip-flexor muscles would reduce the time from muscle activation to production of a force of sufficient magnitude to flex the hip, lift the leg mass against gravity, and eventually relieve the pedal from the mass of the leg.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have reported that the iliopsoas muscle is an important contributor during pedaling. 12 The rectus femoris muscle, which crosses the hip joint like the iliopsoas muscle, but in addition crosses the knee joint, is considered a top transition-extensor muscle, where "top" refers to the top dead center of the crank revolution. 13 Increased rate of force development in the hip-flexor muscles would reduce the time from muscle activation to production of a force of sufficient magnitude to flex the hip, lift the leg mass against gravity, and eventually relieve the pedal from the mass of the leg.…”
Section: Discussionmentioning
confidence: 99%
“…First, the duration of exercise stress testing in our patients was relatively short and the intensity relatively low. By comparison, studies in healthy volunteers involved much more demanding regimens (6,9,15,16). Although our patients achieved a reasonable work load, the exercise capacity in a predominantly elderly group of oncology patients is probably lower than that of healthy (and mostly younger) volunteers in applied physiology protocols.…”
Section: Discussionmentioning
confidence: 77%
“…Exercise-induced 18 F-FDG uptake in skeletal muscles has been studied (9,10,15). With treadmill exercise, 18 F-FDG uptake increases in the soleus, gastrocnemius, gluteal, and quadriceps muscles, followed by adductors and hamstring muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports have quantified muscle activity using 18 F-FDG PET (Fujimoto et al 1996Tashiro et al 1999;Gondoh et al 2009;Shimada et al 2011). Fujimoto et al (1996) were the first to use this method and reported muscle activity during running.…”
Section: Introductionmentioning
confidence: 99%